Water Solubility and Physical Losses and Sulfur and Phosphorus from S-Coated Triple Superphosphates - DANA, MADE (AGRITROP; Vol. 26, No. 3 September 2007, 2012)
Coated fertilizer must retain the coating during transport and handling, but the nutrients in the coat must be released readily in the soil to meet plant demand. Three experimental fertilizer where S is adhered to TSP granules using AD1, AD3 or AD2 adhesive were compared with a commercial S coated TSP, Hifert (HF) Goldphos-10. Fertilizer S loss from the granule was measured in a rotating drum friabilator. The highest particle loss was recorded wit HF, and there were no significant differences recorded between AD1, AD2 and AD3. Release of S from the coated fertilizers was measured by placing the fertilizers between 500 pm nylon mesh and leaching with distilled water at 20 mL min-1 for up to 96 h. In all release was fastest from AD1 and AD3, and the amount of Ca and P released from the granule was also highest with these two products. Granules were scanned in the electron microscope, and electron microprobe both before and after leaching. Dispersion in distilled water was also recorded. The microprobe scan confirmed the leaching data with more S remaining in the granule with HF than AD1 or AD3. These data confirm earlier studies that the method of adhesion of S to TSP can markedly alter the agronomic performance of the fertilizer.
Keywords: sulfur, attrition, granule strength.